PATRIOTIC HYMN IN THE NATIONAL SPIRITUAL HERITAGE (AS AN EXAMPLE OF UZBEK FOLK PROVERBS) (Academia Science Repository, 2023)
The article states that the study of fairy tales and myths, Proverbs and proverbs, examples of the creativity of our ancestors from the samples of folk oral creativity in increasing the national consciousness and ideology of the military operating in the National Army of Uzbekistan gives effective results. Also, Yusuf Khos Hajib's "Kutadgü bilig" from the Eastern thinkers brings an analysis of his thoughts about the state and power, the ruler and his courtiers, their duties and duties, various social classes, their role in the life of society, as well as the military, the quality and characteristics that the Army leaders should possess.